Efficacy and safety of digoxin/furosemide for cutaneous warts: a systematic review and meta-analysis of eight randomized controlled trials - Ahmed Abu-Zaid; Rashed A. Alhusaini; Fai M. Alsaleeli; Danah I. Alkandari; Sayed Hashim; Suad Alassaf; Deemah I. Alkandari; Retaj S. AlJuma; Sarah M. Sabzali; Abdulbadih R. Saad; Ali Ashkanani; Abdullah M. Alharran (Annals of Medicine & Surgery, 2026)
Background: Cutaneous warts, caused by human papillomavirus, are common and often resistant to standard treatments, such as cryotherapy, which have high recurrence rates and side effects. Ionic contra-viral therapy (ICVT), combining digoxin and furosemide, has emerged as a novel therapeutic approach, but its clinical effectiveness remains uncertain. Methods: A comprehensive search of PubMed, Scopus, Google Scholar, CENTRAL, and Web of Science was conducted for randomized controlled trials (RCTs) up to October 2025. Primary outcomes were clinical and dermoscopic response rates; secondary outcomes included recurrence, changes in wart size and number, and adverse events. Risk ratios (RRs) and mean differences (MDs) were pooled using Stata 19 with 95% confidence intervals. Results: Eight RCTs comprising 456 patients were included. Compared with placebo, ICVT significantly improved complete clinical response (RR: 9.27, P < 0.001), reduced recurrence (RR: 0.05, P = 0.01), and decreased wart size (MD: −1.67, P < 0.001). Compared with active controls, ICVT showed similar efficacy, with no significant differences in complete clinical response (RR: 0.98, P = 0.95) or recurrence ( P = 0.56). Notably, ICVT was associated with fewer pigmentation changes (RR: 0.15, P = 0.01) and hemorrhagic bullae (RR: 0.07, P = 0.01) than with active treatments. Conclusion: ICVT demonstrated promising efficacy and a favorable safety profile compared to standard treatments for cutaneous warts. However, due to the low to very low certainty of the current evidence, these findings are preliminary. Further robust, large-scale RCTs are required to confirm its clinical utility and definitively establish its role in standard practice.